2013
DOI: 10.3892/etm.2013.900
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different doses of sufentanil and remifentanil combined with propofol in target-controlled infusion on stress reaction in elderly patients

Abstract: The current study aimed to observe the effects of sufentanil and remifentanil combined with propofol in target-controlled infusion (TCI) on perioperative stress reaction in elderly patients. A total of 80 elderly patients requiring general anesthesia were recruited. They were divided into four groups (each n=20) according to different target concentrations of remifentanil and sufentanil. These target concentrations were: 4 ng/ml remifentanil + 0.2 ng/ml sufentanil for group I; 3 ng/ml remifentanil + 0.3 ng/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…Stress response is a non-specific defense reaction that occurs in the human body when externally stimulated. Previous findings ( 2 , 17 , 18 ) have shown that, stress responses initiated from anesthesia and surgery occur during the perioperative period, with a certain impact on recovery of patients following surgery. Serum COR and blood GLU can reflect t the intensity of stress response in the human body and IL-6 and IL-10 are important cytokines that are involved in the inflammatory response and injury repair and reflect the degree of human stress ( 19 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Stress response is a non-specific defense reaction that occurs in the human body when externally stimulated. Previous findings ( 2 , 17 , 18 ) have shown that, stress responses initiated from anesthesia and surgery occur during the perioperative period, with a certain impact on recovery of patients following surgery. Serum COR and blood GLU can reflect t the intensity of stress response in the human body and IL-6 and IL-10 are important cytokines that are involved in the inflammatory response and injury repair and reflect the degree of human stress ( 19 ).…”
Section: Discussionmentioning
confidence: 98%
“…Sufentanil is a type of narcotic drug and opioid receptor agonist, and contains citrate as the main pharmacological component ( 2 4 ). Sufentanil is easily transferred through the blood-brain barrier with its high lipid solubility, and can bind with plasma protein for a good analgesic effect, with a longer interval for anesthesia ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufentanil is a strong analgesic drug, and can be used repeatedly; in addition, it does not produce accumulation effect and thereby the impact on the cardiovascular system is weak. 7 Anesthesia and surgery can cause intense stress response and in stress stimulation of surgery and tumor; the patients will release a large number of inflammatory factors which have important influence on the therapeutic effect and prognosis of surgery. Previous studies show that the mechanism of systemic inflammatory response caused by surgery is very complex.…”
Section: Discussionmentioning
confidence: 99%
“…use of TCI enables the efficient, safe, and stable administration of sufentanil. 19,20 Combined administration of inhaled anesthetics and sufentanil has been widely used. Meaudre et al 21 found that 0.30 lg/kg sufentanil supplementation of sevoflurane during induction of anesthesia resulted in a better quality of induction without significant cardiovascular depression.…”
Section: Discussionmentioning
confidence: 99%